STUDENTS' VOICES ON ACADEMIC WRITING ACTIVITIES AT TERTIARY LEVEL - Furqan, Muhammad; Rahmawati Nur, Maulidia; Athifah, Syfa (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2021)
Academic writing activities play an important role for students at the tertiary level. Because students are required to be mastered to write academically. The aim of this research was to know-how is the teaching of writing for academic purposes, to know how students perceive the teaching of writing for academic purposes, and to know how a teacher perceives the teaching of writing for academic purposes. Case study was used as the research design in the paradigm of the qualitative and 20 students (in the 5th semester) and 1 teacher from Bogor Ibn Khaldun University were invited as a research participant. Observation, interview, photovoice, voice recorder, and documents were used as a research instrument to get the data. The result of this study showed the teacher taught the materials before each student was required to write an essay. The teacher provided feedback and comment on their essay in the process of writing an essay. Students did the revising process to make their essays better. The students also had a positive perception of the teaching of writing for academic purposes. There were three aspects that students perceive on the teaching writing for academic purposes those were the teaching practice, teachers' feedback, and students' problems or challenges. Besides, the teacher perceives there were some problems encountered in the teaching of writing for academic purposes. The problems encountered were students' level proficiency, students' motivation, technical problems in the classroom, the production of the students' essay, and the support from the leader.